Correlation measurement of propagating microwave photons at millikelvin - Aarne Keränen; Qi-Ming Chen; András Gunyhó; Priyank Singh; Jian Ma; Visa Vesterinen; Joonas Govenius; Mikko Möttönen (Nature Communications)
Abstract Microwave photons are essential carriers of quantum information in several promising platforms for quantum computing. However, measurement of the quantum statistical properties of microwave photons is demanding owing to their low energy relative to thermal fluctuations of any room-temperature detector, and phase-insensitive voltage amplification necessarily adds noise. Here, we overcome this trade-off with a nanobolometer that directly measures the photon statistics at millikelvin. Using a cryogenic temperature-controlled blackbody radiator, we demonstrate the detection of the mean photon number $$\langle \hat{n}\rangle$$ ⟨ n ̂ ⟩ and reveal the expected photon number variance $${(Δ n)}^{2}=\langle \hat{n}\rangle \left(\langle \hat{n}\rangle+1\right)$$ ( Δ n ) 2 = ⟨ n ̂ ⟩ ⟨ n ̂ ⟩ + 1 , following the Bose–Einstein distribution. By engineering the coherent and incoherent proportions of the input field, we observe a transition between super-Poissonian and Poissonian statistics from the bolometric second-order correlation measurements. This technique is poised to serve in fundamental tests of quantum mechanics and function as a scalable readout solution for a quantum information processor.